Analisis Buku Paket Matematika Siswa SMP/MTs Kelas VII Semester 1 Kurikulum 2013 Berdasarkan Kriteria Bell - Ida Ayu Putu Semaraning Tyas; Ketut Sarjana; Syahrul Azmi; Nani Kurniati (Griya Journal of Mathematics Education and Application, 2021)
The purpose of this study is to describe the mathematics textbook for students grade seven of Junior High School semester 1 of the 2013 curriculum in terms of the material eligibility, the method of delivering the material, and the physical character of the book according to Bell's criteria. Therefore, the type of research used is descriptive research with a qualitative approach. The collecting data uses documentation techniques in form of books and questionnaire techniques in form of questions based on Bell's criteria which have been declared valid and suitable to be used. Data collection was carried out directly where the researcher made face-to-face meetings with the teacher at school. The results obtained show that the suitability of the material to Bell's criteria contributed from CHAPTER I to CHAPTER IV has a percentage of 86.90% with a very good category, the suitability of the material delivery method to Bell's criteria contributed from CHAPTER I to CHAPTER IV has a percentage of 71.43% in the good category and the physical character of the book has a percentage of 81.81% with the very good category.